Etika Guru dan Peningkatan Kualitas Pendidikan Agama Hindu - Dewi Sinta; Putu Diapurnaman; Agung Adi (Institut Agama Hindu Negeri Tampung Penyang Palangkaraya, 2025)
Public debates on the quality of education in Indonesia are often marked by empirical assumptions that place doubts on educational outcomes by attributing them primarily to the low professionalism of teachers. Such assumptions tend to oversimplify the problem, given that education is inherently a complex system involving interrelated structural, cultural, pedagogical, and ethical dimensions. Prematurely justifying teachers as the sole determinant of educational shortcomings therefore requires critical reexamination. This article aims to analyze issues of educational quality, with specific attention to Hindu Religious Education, through the lens of teacher ethics derived from Hindu teachings. The shift in the essence of the educator’s role, from the teacher as a moral authority, value bearer, and role model toward learning paradigms that emphasize student-centered activity, is viewed as potentially generating ethical tension when not accompanied by strong moral integrity and responsibility on the part of teachers. Within this context, religion is positioned as a primary source of ethical and moral values with a strategic function in the formation of a civilized society. Hinduism, as one of the religious subjects taught in Indonesian schools, contains a rich corpus of ethical teachings that remain highly relevant as foundations for teacher professionalism. This study employs a qualitative descriptive approach based on a literature review of Hindu scriptures, academic works, and relevant prior studies. The discussion focuses on the nature of ethics in Hindu teachings, the concept of the teacher within Hindu tradition, and the application of sattvic qualities, wiweka (moral discernment), honesty, wisdom, and justice in the teaching and learning process. The findings indicate a persistent gap between the ethical ideals of Hindu teachings and the actual practice of Hindu religious instruction in schools, which remains predominantly oriented toward cognitive achievement rather than lived experience, moral exemplarity, and practical application of values. Consistent integration of Hindu ethics into pedagogical practice is therefore expected to enhance the quality of Hindu Religious Education by balancing cognitive, affective, and psychomotor domains while strengthening the teacher’s role as an agent of dharma within the educational system